Definitions, terminology, and related concepts of “racial health equity”: a scoping review protocol - Heyn, Patricia C.; Terhune, Elizabeth A.; Dagne, Mahederemariam B.; Piper, Christi; Welch, Vivian A.; Francis, Damian; Pizarro, Ana B.; Rizvi, Anita; Sathe, Nila; Dewidar, Omar; Ovelman, Colleen; Duque, Tiffany; et al. (Université d'Ottawa | University of Ottawa, 2023)
Abstract Background In the USA, access to quality healthcare varies greatly across racial and ethnic groups, resulting in significant health disparities. A new term, “racial health equity” (RHE), is increasingly reported in the medical literature, but there is currently no consensus definition of the term. Additionally, related terms such as “health disparities,” “health inequities,” and “equality” have been inconsistently used when defining RHE. Methods The primary purpose of this scoping review is to investigate the current use and underlying concepts used to define racial health equity. The study will address two key questions: (1) “What terminology and definitions have been used to characterize RHE?” and (2) “What knowledge gaps and challenges are present in the current state of RHE research and theory?” The review will collect and analyze data from three sources: (1) websites from key national and international health organizations, (2) theoretical and narrative published articles, and (3) evidence synthesis studies addressing interventions targeting racial health equity and minority stakeholder engagement. Discussion Defining “racial health equity” and related terminology is the first step to advancing racial health equity within the USA. This review aims to offer an improved understanding of RHE constructs and definitions, bringing greater unity to national racial health equity research efforts across disciplines. Systematic review registration This protocol is registered with the Open Science Framework at https://osf.io/7pvzq .